The Influence of Chinese Social Sciences: Publication, Collaboration, and Citation Trends - Demeter, Márton; Goyanes, Manuel; Háló, Gergő; Xu, Xin (International Higher Education, 2025)
<h3 id="the-internationalization-of-chinese-social-sciences-is-explored-through-publication-collaboration-and-citation-trends-in-the-fields-of-economics-education-and-political-science-analysis-of-8962-scopus-indexed-publications-from-2016-to-2020-highlights-global-impact-disciplinary-silos-and-westernization-in-research-practices" data-pm-slice="1 1 []">The internationalization of Chinese social sciences is explored through publication, collaboration, and citation trends in the fields of economics, education, and political science. Analysis of 8,962 Scopus-indexed publications from 2016 to 2020 highlights global impact, disciplinary silos, and “Westernization” in research practices.